Development and validation of a health and nutrition empowerment module for the Women's Empowerment in Agriculture Index - Heckert, Jessica (International Food Policy Research Institute, 2018)
Presented by Jessica Heckert (IFPRI/A4NH), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.